A Graph Grammar Approach to the Design and Validation of Floor Plans. (12th February 2019) - Wang, Xiao-Yu; Liu, Yu-Feng; Zhang, Kang
ABSTRACT: Researchers have proposed many approaches to generate floor plans using shape grammars. None of them, however, testifies the semantic relations among rooms. This paper presents a generic approach for grammar specification, grammar induction, validation, and design generation of house floor plans using their path graphs based on the reserved graph grammar (RGG) formalism. In our approach, the connectivity of a floor plan is analyzed by user-specified graph grammar transformation rules, also known as productions . Floor plans of houses in different styles share common attributes while retaining specific features. By identifying these features, our approach validates floor plans in different styles with user-specified graph productions. A graph grammar induction engine is also introduced to assist designers by automatically inferring graph productions from an input graph set. In addition, the derivation process in RGG offers the capability of generating floor plan designs. Two types of constraints, specified as attribute-sets, are introduced to generate floor plans meeting a wide range of requirements. To evaluate this generic approach, we design a set of productions to validate and generate floor plans in the style of Frank Lloyd Wright's prairie houses. The results are discussed, and further research is suggested.